Bacterial role in pine wilt disease development – review and future perspectives. Issue 1 (24th September 2014) - Nascimento, Francisco X.; Hasegawa, Koichi; Mota, Manuel; Vicente, Cláudia S. L.
Summary Mutualistic and beneficial relationships between nematodes and bacteria are highly present in nature, mostly occurring because of nutritional dependence and pathogen protection, and intrinsically related with the environment, the ecological conditions and the nematode life stages. Thirty‐four years have passed since the first hypothesis suggesting a bacterial role in pine wilt disease (PWD), associated with the pinewood nematode (PWN), Bursaphelenchus xylophilus. In 1980, researchers reported that bacteria associated with the PWN could produce toxins that lead to PWD development in pine seedlings. It was also suggested a double vector system for PWD, where bacteria were vectored by the PWN and the PWN vectored by an insect from the Monochamus genus. Presently, the specific involvement of bacteria in such complex disease is still controversial, even though the increased number of studies focused on the potential bacteria role has increased considerably. This review is an up‐to‐date comprehensive perspective and brings new insights on the role of PWN‐associated bacteria in PWD.